Rewriting, new drafts, new editions: authorial and ecdotic practices (Prassi Ecdotiche della Modernità Letteraria, 2019)
The lexicon about ‘rewriting’, usually employed by Italian scholars, is not shared by all them: in fact, terms such as ‘redazione’, ‘stesura’, ‘revisione’, ‘rielaborazione’, ‘rifacimento’, can be used to denote both similar and completely different case-studies or concepts. The aim of this paper is to elucidate this complex situation by means of two case studies and the terminology used in the field of library sciences. We also suggest some possible solutions to this vagueness, trying to identify the liaison points between theoretical studies, editorial criteria and author’s choice.
Keywords: rewriting; writing; revision; editorial board; philological terminology; Pasquali; Contini; Folena; Caretti; De Robertis; Elio Vittorini; Gesualdo Bufalino